Physics and applications of terahertz metagratings - Shreeya Rane; Shriganesh Prabhu; Dibakar Roy Chowdhury (Opto-Electronic Science)
One dimensional sub-wavelength gratings, also known as metagratings have attracted enormous attention due to the relatively simpler design configurations with versatile application potentials. In recent times, these metagratings have played crucial roles in terahertz frequency domain to realize several fascinating effects. It has been demonstrated that the terahertz characteristics of these metagratings can be modified by carefully designing the grating geometry along with meticulously tuning the material characteristics. Such variations in grating design have led to enhanced device performances. In addition, suitably designed metagratings are capable of exciting strong evanescent orders that can be exploited in ultrasensitive sensing, optical trapping, non-linearity, etc. Based on the tremendous potentials offered by the planar geometry (ease of fabrication) along with diverse utilities, we have reviewed few representative works pertaining to terahertz metagratings in this article. Hence, we have discussed metagratings based antireflection coating and a polarization beam splitter operating in THz region modelled using simplified model method. Further, we have discussed experimental detection of evanescent waves excited in metagratings utilizing Fourier transformed terahertz spectroscopy (FTTS) technique. FTTS is a unique technique because of its ability of simultaneous detection of propagating and non-propagating orders. Next, we have discussed applications of metagratings in sensing trace amount of analytes. Considering the increasing interests in these one-dimensional artificial subwavelength structures, we believe, our article will be useful for the researchers willing to begin work on terahertz subwavelength gratings.